2008
DOI: 10.1007/s12160-008-9047-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Associations with Waterpipe Tobacco Smoking among U.S. University Students

Abstract: Background-Although waterpipe tobacco smoking seems to be increasing on U.S. university campuses, these data have come from convenience samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
314
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(347 citation statements)
references
References 22 publications
27
314
4
2
Order By: Relevance
“…This is in agreement with an earlier study of Poyrazoglu et al (2010) who reported that gender has significant effects on the prevalence of shisha smoking. Male gender was associated with shisha smoking in a number studies Primack et al, 2008;2010). Maziak et al (2004) reported that the shisha smoking was more common among older and male students.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with an earlier study of Poyrazoglu et al (2010) who reported that gender has significant effects on the prevalence of shisha smoking. Male gender was associated with shisha smoking in a number studies Primack et al, 2008;2010). Maziak et al (2004) reported that the shisha smoking was more common among older and male students.…”
Section: Discussionmentioning
confidence: 93%
“…According to reports of Ward et al (2007) and SmithSmione et al (2008), many shisha smokers do not see themselves as addicts and there is a common perception among shisha users the that they can quit whenever they want. Likewise, Primack et al (2008) reported that 52% of college students believed shisha are less addictive than cigarettes. However, the perception that shisha smoking is not as addictive as smoking cigarette is proven to be wrong .This is evidenced by the studies which revealed that approximately half of the respondents still returned to shisha smoking after trying to quit it (Marziak et al, 2004;Jackson andAveyard, 2008, Mohammed et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 6.3% of the students (n=79) believe that waterpipe is not harmful because its smoke does not burn the lungs, 25.33% (n=318) think that the carcinogenic chemicals are filtered while waterpipe smoke passes from the water and 4.24% have no idea. In the studies, it is emphasized that waterpipe smoking has many risks such as lung diseases and cancer (Knishkowy et al, 2005;Primack et al, 2008;Noonan et al, 2009;Akl et al, 2010;Abughosh et al, 2012). A recent systematic review of studies of health effects of waterpipe smoking shows that waterpipe smoking doubles the risk of lung cancer (Akl et al, 2010;Maziak, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, 12.11% of the students (n=152) replied "yes" to the statement "Waterpipe contains no nicotine" while 0.64% replied "I have no idea" to this statement. In the studies, waterpipe smoking is declared to cause nicotine addiction (Knishkowy et al, 2005;Primack et al, 2008;Noonan et al, 2009;Abughosh et al, 2013). In the study, it is seen that 14.02% of the students (n=176) think waterpipe with fruit/aroma is healthier than plain waterpipe, 1.2% have no idea about the issue.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization states that one hookah smoking session may be equivalent to inhaling as much smoke as using 5 packs of cigarettes 12 . Despite this, however, hookah is often perceived as a safer and less addictive alternative to cigarettes, especially among young people 13,14 . While some studies have described female gender…”
Section: Introductionmentioning
confidence: 99%